The Influence of Work Environment, Leadership and Motivation on The Performance of Nurses at Hati Mulia Hospital - Handris; Ridwan, Muhammad; Indahlestari, Wa Ode Dien; Nurhalisa (International Journal of Management and Education in Human Development, 2023)
This study aims to test or analyze the influence of the work environment, leadership, and motivation on the performance of Nurses at Mulia Hati Hospital. This research is a quantitative approach. The population in this study were Nurses at Hati Mulia Hospital with a sample of 51 people. The analysis used multiple linear regression analysis with the help of IBM SPSS 24 Software. The results showed that simultaneously the work environment, leadership, and motivation had a positive and significant effect on the performance of Nurses at Hati Mulia Hospital, partially, the work environment had a positive and significant effect on Nurse performance At Hati Mulia Hospital, leadership has a positive and significant effect on the performance of Nurses at Hati Mulia Hospital and motivation has a positive and significant effect on the performance of Nurses at Hati Mulia Hospital.